REFLECTION PROBLEMS OF POLYGAMY DEBATES IN STRUCTURAL GENDER AND MODERNIZATION - Dedeh Saadah (Awang Long Law Review, 2022)
A wife can only have a husband only if a wife wants and because of several factors that require the husband to have another wife such as the wife cannot fulfill her obligations etc. The court can give permission to the husband for more than one person, but for now polygamy is implemented only to fulfill satisfaction without realizing there are many negative impacts that will occur when you have fulfilled polygamy not the wife's mentality, but also their children who must be visited, for husbands who marry without the permission of the legal wife can be penalized but there are plans for wives who cannot be punished ask for permission.